Simulation-Based Internal Models for Safer Robots - Blum, Christian; Winfield, Alan F. T.; Hafner, Verena V. (Frontiers in Robotics and AI, 2018)
In this paper we explore the potential of mobile robots with simulation-based internal models for safety in highly dynamic environments. We propose a robot with a simulation of itself, other dynamic actors and its environment, inside itself. Operating in real-time this simulation-based internal model is able to look ahead and predict the consequences of both the robot's own actions and those of the other dynamic actors in its vicinity. Hence the robot continuously modifies its own actions in order to actively maintain its own safety while also achieving its goal. Inspired by the problem of how mobile robots could move quickly and safely through crowds of moving humans, we present experimental results which compare the performance of our internal simulation-based controller with a purely reactive approach. These experiments show that the safety of the robot can be significantly improved subject only to the additional computational cost of running a simulation-based internal model.